Hubungan Pengetahuan Beauty Therapist dengan Implementasi Sistem Pengelolaan Sampah 3R (Reduce, Reuse, Recycle): The Relationship Between Beauty Therapists' Knowledge and the Implementation of the 3R (Reduce, Reuse, Recycle) Waste Management System - Wulandari, Endang Sri Purwanti; Sunarta, Elfania Arumma (Chakra Brahmanda Lentera Institute, 2026)
Waste management based on the 3R principles (Reduce, Reuse, Recycle) in beauty clinics is an important effort to maintain environmental health and prevent the negative impacts of both medical and non-medical waste. The low implementation of proper waste management standards remains a problem influenced by the knowledge level of health workers. This study aims to determine the relationship between the knowledge of health workers and the implementation of 3R-based waste management in beauty clinics in the Banyuwangi area. This study used a descriptive analytic design with a cross-sectional approach. A total of 20 respondents were selected using purposive sampling. The research instruments included a knowledge questionnaire and an observation sheet on 3R implementation. Data analysis was performed using the Spearman Rank test. The results showed that most respondents had good knowledge (70%) and good implementation of 3R practices (60%). Statistical analysis indicated a significant relationship between the knowledge of health workers and the implementation of 3R-based waste management (p-value = 0.021). It can be concluded that the better the knowledge of health workers, the better the implementation of 3R-based waste management in beauty clinics. Continuous education and training are needed to support more optimal and sustainable waste management practices.